A Multi-Layered Analysis of Dancing in Eighteenth-Century French Opera. (November 2015) - Dartois-Lapeyre, Françoise; McGowan, Margaret M.
Abstract : This article offers an analysis of the contribution of dance to the success of French opera in the eighteenth century. It explores its development as it responded to the needs of music and song; its capacity to blend with evolving opera forms fitting in and commenting upon the décor itself; and draws out the inventiveness of successive generations of performers and choreographers who ensured that the works of Lully, Campra and Rameau continued to respond to changing public taste. From this analysis, dance emerges as the barometer by which we can measure the superiority of French over Italian opera, as it paved the way for the creation of ballet d'action.